The gendered business and human rights regime: a review of Colombia's decalogue for gender equity in the mining sector (2020)
Gendered Business and Human Rights (Gendered BHR) has become an international regime complex that elaborates on the role of companies in the promotion of gender equality. Two paradigms form this regime: A marked-based paradigm that stages a business case, embodied in the Women's Empowerment Principles; and a rights-based paradigm articulated in the Gender Dimension of the UN Guiding Principles of BHR. This paper explores the logics and limitations behind Gendered BHR taking as a case study the Colombia's Decalogue for Gender Equity in the Mining Industry. It is argued that, even when a rights-based instrument that intends to address unequal power relations based on gender in the corporate world is available, the business case has become the hegemonic paradigm for companies and countries. However, by instrumentalizing gender equality for obtaining profitability and economic growth, the business case approach weakens the transformative potential of women's empowerment and thus, presents substantial limits to achieve women's emancipation